PEMBERDAYAAN PENDIDIKAN ANAK-ANAK PKL DI SURAKARTA - Sarjono, Yetty; Suyatmini, Suyatmini (PROCEEDING, 2012)
PEMBERDAYAAN PENDIDIKAN ANAK-ANAK PKL DI SURAKARTA  Yetty Sarjono1, dan Suyatmini2 1,2Dosen Pendidikan Akuntansi FKIP, dan Magister Manajemen Pendidikan Pascasarjana, Universitas Muhammadiyah Surakarta.  AbstractThe purpose of this study is expected to be able to find the exact model of the arrangement of street vendors can optimize their income. With proper arrangement of street vendors are expected to provide constructive solutions to empower their childrens education level. The method used was qualitative, with the perspective of phenomenology, the research subjects of the street vendors, children, and city officials. Medium types and data sources are the words and actions, data collection techniques using observation techniques, interviews, making field notes, and use documents. Data analysis starts from the collection of data, arrange the points of findings, presentation of data and drawing conclusions with an analysis of the phenomenology of Schutzbecause motive and in order to motive.The results of this study is that the model of vendor arrangement using a persuasive approach and consider the human element. In the structural model of the arrangement of street vendors is done through five types of models, namely: a. Shelter, b. Tents Umbrellas, c. Ordinary tents, d. Gerobag, and e. Roads, according to the condition of each street vendors. Vendors understanding of the empowerment level of education of their children is: Because are: First, because during this time many of their children are neglected and can not continue their education due to lack of school fees. Second, because of the increased revenue then there is a strong willingness to continue the education of their children to pursue higher degrees. Third, because they are on average willing to improve and add to his wares. According to in order to motive are: First, in order not to move at any time, thus making their efforts can be successful to be able to finance their childrens schooling. Second, that the children stay in school, so that later is better than the fate of his parents. Third, that the future of her children more independent because of the increased motivation to learn them, especially for completing vocational education level.  Key words: settlement model, empowerment, education level.